Impact of Jeera Water On Gastritis: A Quasi-Experimental Study - Ms Lakshmi HN; Mr. Prashanth D; Mrs Ramai P; Dr Shivanna Malini (International Journal of Pharma and Bio Sciences, 2024)
Gastritis is the most common disorder of the upper digestive tract. It is a common health problem among young adults. It may be acute or chronic. Gastritis remains a social and public health problem in developed and developing countries. Kala Jeera (Nigella Sativa) releases healthy enzymes that speed the body’s digestion processes and aid in the smooth breaking down of stern fat, sugars, and carbohydrates. It is also rich in anti-inflammatory and antioxidant properties that ensure a smooth digestion process. Many over-the-counter drugs, claiming to give relief, are introduced overnight and then hurriedly withdrawn on findings of serious side effects. Under these circumstances, a tried and tested remedy over centuries can be far more safely relied upon. The current study aimed to determine the potential benefits of Kala Jeera water for Gastritis. Using a quasi-experimental design, fifty patients were selected randomly(n=50) who fulfilled inclusion and exclusion. A purposive sampling technique was used to select the patients. The data was collected by using a modified gastrointestinal questionnaire. Pretest scoring was done using a modified gastrointestinal questionnaire. After that, the subjects were given Jeera Water and advised to continuously drink on an empty stomach early morning, once a day for 4 weeks. A post-test was conducted after 4 weeks of using a self-administration modified gastrointestinal questionnaire. Pretest and post-test scores were compared. There is a significant reduction in symptoms like abdominal bloating, belching after meals, vomiting after eating, constipation or diarrhea, and coated tongue after 4 weeks. Data analysis revealed that Kala Jeera water effectively reduced Gastritis. We conclude that Kala Jeera water is a cost-effective natural gastritis remedy without any side effects. And it is a simple process. Keywords: Gastritis is the most common disorder of the upper digestive tract. It is a common health problem among young adults. It may be acute or chronic. Gastritis remains a social and public health problem in developed and developing countries. Kala Jeera (Nigella Sativa) releases healthy enzymes that speed the body’s digestion processes and aid in the smooth breaking down of stern fat, sugars, and carbohydrates. It is also rich in anti-inflammatory and antioxidant properties that ensure a smooth digestion process. Many over-the-counter drugs, claiming to give relief, are introduced overnight and then hurriedly withdrawn on findings of serious side effects. Under these circumstances, a tried and tested remedy over centuries can be far more safely relied upon. The current study aimed to determine the potential benefits of Kala Jeera water for Gastritis. Using a quasi-experimental design, fifty patients were selected randomly(n=50) who fulfilled inclusion and exclusion. A purposive sampling technique was used to select the patients. The data was collected by using a modified gastrointestinal questionnaire. Pretest scoring was done using a modified gastrointestinal questionnaire. After that, the subjects were given Jeera Water and advised to continuously drink on an empty stomach early morning, once a day for 4 weeks. A post-test was conducted after 4 weeks of using a self-administration modified gastrointestinal questionnaire. Pretest and post-test scores were compared. There is a significant reduction in symptoms like abdominal bloating, belching after meals, vomiting after eating, constipation or diarrhea, and coated tongue after 4 weeks. Data analysis revealed that Kala Jeera water effectively reduced Gastritis. We conclude that Kala Jeera water is a cost-effective natural gastritis remedy without any side effects. And it is a simple process.